FAKTOR INTERNAL YANG BERHUBUNGAN DENGAN KEPATUHAN ASUHAN ANTENATAL IBU HAMIL DI PUSKESMAS TELADAN - HINDI JUANA PUTRI; IKA NOPA (JURNAL ILMIAH MAKSITEK, 2021)
Currently in Indonesia every day there is a mother's death associated with pregnancy, childbirth, and Nifas, the World HealthOrganization (WHO) reports that mother's death is estimated as much as 500,000 deaths annually and 99% of which areoccurring in developing countries. Through asuhan antenatal visits, any complications that may or will arise in the pregnancyare known, and can immediately be resolved before a good effect on the pregnancy. Internal factors are very responsible forpregnant women doing Asuhan antenatal, some of the internal factors are the reason for his doing and not to do Asuhanantenatal routinely. Internal factors include parity, education, employment and a person's age. To know the relationshipbetween age, education, parity, employment, with the adherence of Asuhan antenatal visits in Puskesmas Teladan,Kecamatan Medan kota, province of North Sumatra. Descriptive analytic by using cross sectional design. Data obtained isprimary data with 50 samples and then conducted analysis with Chi Square test. The chi-square test results show that thereis an age relationship of pregnant women to the compliance of asuhan antenatal visits is P = 0.016 (P < 0.05), the level ofeducation of expectant mothers on the compliance of asuhan antenatal visits is P = 0.001 (P < 0.05), the parity of asuhanantenatal visit compliance is P = 0.036 (P < 0.05), and the work of the asuhan antenatal visit compliance is P = 0.001 (P <0.05). There is a relationship between the ages, the education of parity and employment to the compliance of asuhanantenatal visits of pregnant mothers in Puskesmas Teladan, Medan kota, province of North Sumatera.